Methods of Increasing Labor Efficiency Indicators - Suvanov, Bekniyoz Bakhtiyar ugli (RA Journal of Applied Research, 2023)
This article talks about proposals and problems for increasing labor efficiency indicators in economic entities. In the conditions of the modern market economy, the development and competitiveness of the organization directly depends on labor efficiency. The greater the labor efficiency, the more products are created per unit of time, and as a result, the total output of the enterprise increases. Therefore, increasing labor productivity is one of the most important tasks of any enterprise.